2008
DOI: 10.3758/pbr.15.3.667
|View full text |Cite
|
Sign up to set email alerts
|

Object manipulability affects children's and adults' conceptual processing

Abstract: A large body of evidence from developmental psychology, cognitive psychology, and neuropsychology supports the idea that there are different kinds of concepts. Artifact concepts would be mostly characterized by function, whereas natural kinds would be predominantly organized around perceptual information. Numerous studies in children show that functional similarities drive induction, name generalization, and categorization for artifacts from

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
30
0
6

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 43 publications
3
30
0
6
Order By: Relevance
“…For example 'keylock' , 'feet -slippers' are thematically related in spatial as well as functional aspects, compared to 'car -road' which has only spatial attribute or 'tumbler -plate' which has mainly temporal attribute. Similar results were found in previous studies where participants made more thematic choices, when thematic relationship involved a direct, functional interaction than when it did not [34,35].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…For example 'keylock' , 'feet -slippers' are thematically related in spatial as well as functional aspects, compared to 'car -road' which has only spatial attribute or 'tumbler -plate' which has mainly temporal attribute. Similar results were found in previous studies where participants made more thematic choices, when thematic relationship involved a direct, functional interaction than when it did not [34,35].…”
Section: Discussionsupporting
confidence: 90%
“…Hence, the visual perspective of something, such as a picture or object, is actually an experience of perception, action, and introspection [33]. The results of the study are in consonance with the observations made by earlier studies who reported that functional relations, which play an important role in thematic conceptual relations, were particularly relevant for physically manipulable object concepts [34,36]. They suggested that functionally interactive pairs are defined by their real-world physical actions and spatial relationships (i.e., manipulability) than non interactive pairs.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In other words, the movement patterns of living things are perceptually (and functionally) distinct from the movement patterns of nonliving things, a notion that is echoed both in neuropsychological and neuroanatomical models of adult semantic processing (e.g., Beauchamp, Lee, Haxby & Martin, 2002;Tyler, Moss, Durrant-Peatfield & Levy, 2000). In fact, in a recent study using a picture-matching task, both children and adults demonstrated faster reaction times when identifying "contextual/functional" relationships for manipulable objects, whereas reaction times were faster when identifying "perceptual similarity-based" relations for nonmanipulables, particularly those from living categories (Kalénine & Bonthoux, 2008).…”
mentioning
confidence: 99%
“…A large literature has addressed how children first group items: taxonomically (e.g., apple-banana) or thematically (e.g., apple-pie). Several researchers have pointed out that taxonomic organization might be based more on perceptual input, while thematic organization might be based more on conceptual input (e.g., Kalénine & Bonthoux, 2008). Organization and enrichment of one's semantic network likely happens through learning based on both perceptual and conceptual organization schemes from within the first year of life.…”
mentioning
confidence: 99%